PENGARUH DESA WISATA TERHADAP PERUBAHAN PENGGUNAAN LAHAN, EKONOMI, SOSIAL BUDAYA MASYARAKAT DI SEKITAR DESA WISATA - Qotrunnada, Rifdah; Karmilah, Mila (Universitas Islam Sultan Agung, 2024)
Tourism is a tourism activity that is realized in the form of activities or travel activities. Tourism activities must be supported by the availability of adequate facilities and infrastructure so that these activities can take place optimally and sustainably. According to the 2016 Ministry of Tourism Pocket Book, tourism contributed 9% to National GDP or Rp 946.09 trillion. Tourism contributes to the country's foreign exchange of Rp 120 trillion and provides employment to 11 million people. Currently, tourism is realized by what is called a Tourism Village which has the meaning of a community or society consisting of residents in a limited area having direct interaction in a management which has the care and awareness to coordinate with each other to build and be formed to empower the community as the main actors in the administration of the Tourism Village. In its development, Tourism Villages continue to develop in almost every province in Indonesia and participate in influencing the daily activities of the villagers. The purpose of this study was to determine the impact caused by the existence of the Tourism Village on changes in land use, economy, socio-culture, and the community environment around the Tourism Village using the literature review method. Based on the results of the studies that have been carried out, several indicators and parameters were found based on variables. The findings show that there is an influence caused by the existence of a tourist village on land use, economy, socio-culture in the community in the Tourism Village area.